Both diversity and functional composition affect productivity and water use efficiency in experimental temperate grasslands. (12th September 2021) - Walde, Manuel; Allan, Eric; Cappelli, Seraina L.; Didion‐Gency, Margaux; Gessler, Arthur; Lehmann, Marco M.; Pichon, Noémie A.; Grossiord, Charlotte
Abstract: Many experiments have shown that biodiversity promotes ecosystem functioning and stability and that this relationship varies with resource availability. However, we still have a poor understanding of the underlying physiological and ecological mechanisms driving diversity effects and how they may interact with soil nutrient availability. We collected data in a grassland experiment factorially manipulating fertilization, species richness (SR), functional composition (slow‐growing vs. fast‐growing species) and functional diversity in resource economic traits. We measured above‐ground productivity (AP), nitrogen (N) uptake, photosynthesis and water use efficiency by combining a 15 N labelling approach with productivity, gas exchange and stable isotope measurements in 3 years differing in rainfall. We found that sown SR increased AP, N uptake and photosynthesis, suggesting that SR is the most important driver of ecosystem productivity and nutrient cycling. Similarly, photosynthesis was affected by functional composition but not by functional diversity. Water use efficiency was reduced by sown SR for communities dominated by slow‐growing species but not for communities dominated by fast‐growing species. Fertilization increased productivity, N uptake and water use efficiency. The positive effects of high SR on ecosystem functions were independent of fertility levels. Synthesis . Our results provide evidence that high species richness in temperate grasslands could enhance productivity and reduce the negative impacts of drought events. Multiple factors and community characteristics are important in driving enhanced ecosystem functioning in biodiverse grasslands and seem to affect functioning and stability through different mechanisms. Abstract : Our results provide evidence that high species richness in temperate grasslands could enhance productivity and reduce the negative impacts of drought events. Multiple factors and community characteristics are important in driving enhanced ecosystem functioning in biodiverse grasslands and seem to affect functioning and stability through different mechanisms.